2002
DOI: 10.1590/s0100-879x2002000100003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of renin mRNA expression and enzyme activity in rat and mouse mesangial cells

Abstract: Renin is an enzyme involved in the stepwise generation of angiotensin II. Juxtaglomerular cells are the main source of plasma renin, but renin activity has been detected in other cell types. In the present study we evaluated the presence of renin mRNA in adult male Wistar rat and mouse (C-57 Black/6) mesangial cells (MC) and their ability to process, store and release both the active and inactive forms of the enzyme. Active renin and total renin content obtained after trypsin treatment were estimated by angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…Gene and protein expression of angiotensinogen (Aogen), renin and ACE has been reported in cultured glomerular mesangial cells [12][13][14][15][16][17][18][19][20][21][22][23][24] and podocytes. [25][26][27][28] Mesangial expression of Aogen and ACE has also been documented in renal tissue sections.…”
Section: Intrarenal Raasmentioning
confidence: 99%
“…Gene and protein expression of angiotensinogen (Aogen), renin and ACE has been reported in cultured glomerular mesangial cells [12][13][14][15][16][17][18][19][20][21][22][23][24] and podocytes. [25][26][27][28] Mesangial expression of Aogen and ACE has also been documented in renal tissue sections.…”
Section: Intrarenal Raasmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that glomerular mesangial cells express mRNA for renin, AGT, and ACE (1). Moreover, mesangial cells in culture are able to synthesize and secrete renin, prorenin, and ANG II and contain both the AT 1 receptor and the prorenin/renin receptor (1,20,22,23). This cell type has been shown to produce extracellular matrix and contributes to progression of glomerulosclerosis (10).…”
mentioning
confidence: 99%
“…A homolog of ACE, termed ACE2, has been recently discovered, which hydrolyzes ANG I to ANG (1)(2)(3)(4)(5)(6)(7)(8)(9) and ANG II to ANG(1-7) (8). ANG II exhibits the majority of its well-known physiological effects via the angiotensin type 1 (AT 1 ) receptor.…”
mentioning
confidence: 99%
“…While this interpretation does not exclude the possibility that aliskiren could bind to renin that may be present in podocytes (5), mesangial cells (1,21), or trafficking through the mesangial matrix, the data indicate that for aliskiren to accumulate in glomeruli, the presence of renin is not required. This interpretation is consistent with recent findings in mice (11) showing that renal accumulation of aliskiren was not affected by AT 1 receptor deletion (renal overexpression of renin) or Ren1c gene deletion (no renal renin expression).…”
Section: Discussionmentioning
confidence: 98%